2007
DOI: 10.1007/bf03027822
|View full text |Cite
|
Sign up to set email alerts
|

Influence of ammonia on the corrosion behavior of Ti−Al−Zr alloy in 360°C water

Abstract: The influence of ammonia on the corrosion behavior of Ti-Al-Zr alloy was evaluated in pressurized water at 360°C for 600 days. The results of the corrosion test indicated that the addition of ammonia accelerated the corrosion and hydrogen pickup rates. The oxide scales were composed of a double layer structure, and an inner layer was covered by an outer layer of oxide grains. The XRD studies on the oxide scales showed that the anatase-TiO 2 was continuously transformed into rutile-TiO 2 as the corrosion procee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…In China, although most of the primary coolant of NPPs is boron-lithium type, there are still several VVER units whose primary coolant is boron-potassium-ammonia type. In the primary coolant, ammonia can not only act as a pH-controlling agent but also can adjust hydrogen concentration by its radiolysis decomposition (Kysela et al, 1996;Kim et al, 2007). However, the corrosion behavior of the Zr alloys especially Zr-Sn-Nb alloy is rarely considered in the boron-potassium-ammonia water chemistry environment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In China, although most of the primary coolant of NPPs is boron-lithium type, there are still several VVER units whose primary coolant is boron-potassium-ammonia type. In the primary coolant, ammonia can not only act as a pH-controlling agent but also can adjust hydrogen concentration by its radiolysis decomposition (Kysela et al, 1996;Kim et al, 2007). However, the corrosion behavior of the Zr alloys especially Zr-Sn-Nb alloy is rarely considered in the boron-potassium-ammonia water chemistry environment.…”
Section: Introductionmentioning
confidence: 99%
“…Garzarolli et al found a large increase in the corrosion rate of zirconium alloy when tested in 20% NH 4 OH in 400 °C steam, but only in nickel autoclave (Garzarolli et al, 1993). Titanium, which belongs to the same elemental group as zirconium, also shows acceleration in corrosion and hydrogen absorption when tested in 360 °C ammonia aqueous solution (Kim et al, 2002;Kim et al, 2007).…”
Section: Introductionmentioning
confidence: 99%